Biomechanical comparison of pedicle screw fixation strength among three different screw trajectories using single vertebrae and one-level functional spinal unit - Tai, Ching-Lung; Chen, Weng-Pin; Liu, Mu-Yi; Li, Yun-Da; Tsai, Tsung-Ting; Lai, Po-Liang; Hsieh, Ming-Kai (Frontiers in Bioengineering and Biotechnology, 2022)
Three key factors are responsible for the biomechanical performance of pedicle screw fixation: screw mechanical characteristics, bone quality and insertion techniques. To the best of the authors’ knowledge, no study has directly compared the biomechanical performance among three trajectories, i.e., the traditional trajectory (TT), modified trajectory (MT) and cortical bone trajectory (CBT), in a porcine model. This study compared the pullout strength and insertion torque of three trajectory methods in single vertebrae, the pullout strength and fixation stiffness including flexion, extension, and lateral bending in a one-level instrumented functional spinal unit (FSU) that mimics the in vivo configuration were clarified. A total of 18 single vertebrae and 18 FSUs were randomly assigned into three screw insertion methods (n=6 in each trajectory group). In the TT group, the screw converged from its entry point, passed completely inside the pedicle, was parallel to the superior endplate, was located in the superior third of the vertebral body and reached to at least the anterior third of the vertebral body. In the MT group, the convergent angle was similar to that of the TT method but directed caudally to the anterior inferior margin of the vertebral body. The results of insertion torque and pullout strength in single vertebrae were analyzed; in addition, the stiffness and pullout strength in the one-level FSU were also investigated. This study demonstrated that, in single vertebrae, the insertion torque was significantly higher in CBT groups than in TT and MT groups (p < 0.05). The maximal pullout strength was significantly higher in MT groups than in TT and CBT groups (p < 0.05). There was no significant difference in stiffness in the three motions among all groups. The maximal pullout strength in FSUs of MT and CBT groups were significantly higher than the TT groups (p < 0.05). We concluded that either MT or CBT provides better biomechanical performance than TT in single vertebrae or FSUs. The lack of significance of stiffness in FSUs among three methods suggested that MT or CBT could be a reasonable alternative to TT if the traditional trajectory was not feasible.